ASSESSMENT OF PHYSICO-CHEMICAL PROPERTIES OF WANG-MARATHWADI DAM, TEHSIL- PATAN SATARA DISTRICT, MAHARASHTRA, (INDIA). - Bhingardeve L. S.; Kadam M. R. (International Educational Journal of Science and Engineering, 2025)
This paper presents the study of physicochemical parameters of Wang-Marathwadi dam of tehsil Patan, Satara District of Maharashtra state. Monthly changes in physical and chemical parameters such as Water temperature, Transparency, Turbidity, Total Hardness, Chlorides, Phosphates, total dissolved solids, PH, dissolved oxygen, free carbon dioxide, Alkalinity, and Nitrates were analyzed during Monsoon, Post Monsoon and summer season. The work was carried out during the year 2024 (January to Dec.). The results of the present investigation have been discussed from that is clear that the water of this reservoir is not polluted but the variations in physic-chemical parameters were observed as seasonally. The result indicate that the reservoir is non-polluted and the recorded rang of the physicochemical parameters were within the maximum permissible limit. So the water can be used for Domestic, Irrigation and Pisciculture purpose.